Using Whole Genome Sequences to Investigate Adenovirus Outbreaks in a Hematopoietic Stem Cell Transplant Unit - Myers, Chloe E.; Houldcroft, Charlotte J.; Roy, Sunando; Margetts, Ben K.; Best, Timothy; Venturini, Cristina; Guerra-Assunção, Jose A.; Williams, Charlotte A.; Williams, Rachel; Dunn, Helen; Hartley, John C.; Rao, Kanchan; et al. (Frontiers in Microbiology, 2021)
A recent surge in human mastadenovirus (HAdV) cases, including five deaths, amongst a haematopoietic stem cell transplant population led us to use whole genome sequencing (WGS) to investigate. We compared sequences from 37 patients collected over a 20-month period, with sequences from GenBank and our own database of HAdVs. Maximum likelihood trees and pairwise differences were used to evaluate genotypic relationships, paired with epidemiological data from routine infection prevention and control (IPC) records and hospital activity data. During this time period two formal outbreaks had been declared by IPC, while WGS detected nine monophyletic clusters, seven were corroborated by epidemiological evidence and by comparison of single nucleotide polymorphisms. One of the formal outbreaks was confirmed, one was not. Of the five HAdV-associated deaths, three were unlinked, the remaining two considered the source of transmission. Mixed infection was frequent (10%), providing a sentinel source of recombination and superinfection. Immunosuppressed patients harbouring a high rate of HAdV positivity require comprehensive surveillance. As a consequence of these findings, HAdV WGS is being incorporated routinely into clinical practice to influence IPC policy contemporaneously.